Effect of rinsing with ethanol-containing mouthrinses on the production of salivary acetaldehyde - Moazzez, Rebecca; Thompson, Hayley; Palmer, Richard M.; Wilson, Ron F.; Proctor, Gordon B.; Wade, William G. (European journal of oral sciences, 2011)
Moazzez R, Thompson H, Palmer RM, Wilson RF, Proctor GB, Wade WG. Effect of rinsing with ethanol‐containing mouthrinses on the production of salivary acetaldehyde.